The novel sequence Diels-Alder reaction/Ireland-Claisen rearrangement applied to acyclic dienophiles: New insights into the selectivity of the Ireland-Claisen rearrangement - Velker, Joerg; Roblin, Jean Philippe; Neels, Antonia; Tesouro, Ana; Stoeckli-Evans, Helen; Klaerner, Frank-Gerrit; Gehrke, Jan-Stefan; Neier, Reinhard (My University, 1999)
The new dienes 4a-d, 7 and 11 reacted in good yields with acyclic dienophiles like methyl acrylate and diethyl fumarate in the tandem process Diels-Alder reaction/Ireland-Claisen rearrangement. Analysis of the relative configuration of products 5, 6, 8-10 and 12 indicated that preference for the chair or boat transition state of the Ireland-Claisen rearrangement is strongly influenced by the relative configuration of the substituents of the cyclohexene ring.
Keywords: Dials-Alder reaction; Ireland-Claisen rearrangement; tandem reaction; diastereoselectivity; high pressure; ORGANIC-SYNTHESIS; ACRYLOYL CHLORIDE; TANDEM REACTIONS; ALKALOIDS; ACETALS; SHIFT; ESTER; ACID